Women׳s birthplace decision-making, the role of confidence: Part of the Evaluating Maternity Units study, New Zealand. Issue 6 (June 2015) - Grigg, Celia P.; Tracy, Sally K.; Schmied, Virginia; Daellenbach, Rea; Kensington, Mary
Abstract Objective to explore women׳s birthplace decision-making and identify the factors which enable women to plan to give birth in a freestanding midwifery-led primary level maternity unit rather than in an obstetric-led tertiary level maternity hospital in New Zealand. Design a mixed methods prospective cohort design. Methods data from eight focus groups (37 women) and a six week postpartum survey (571 women, 82%) were analysed using thematic analysis and descriptive statistics. The qualitative data from the focus groups and survey were the primary data sources and were integrated at the analysis stage; and the secondary qualitative and quantitative data were integrated at the interpretation stage. Setting Christchurch, New Zealand, with one tertiary maternity hospital and four primary level maternity units (2010–2012). Participants well (at 'low risk' of developing complications), pregnant women booked to give birth in one of the primary units or the tertiary hospital. All women received midwifery continuity of care, regardless of their intended or actual birthplace. Findings five core themes were identified: the birth process, women׳s self-belief in their ability to give birth, midwives, the health system and birth place. 'Confidence' was identified as the overarching concept influencing the themes. Women who chose to give birth in a primary maternity unit appeared to differ markedly in their beliefs regarding their optimal birthplace compared to women who chose to give birth in a tertiary maternity hospital. The women who planned a primary maternity unit birth expressed confidence in the birth process, their ability to give birth, their midwife, the maternity system and/or the primary unit itself. The women planning to give birth in a tertiary hospital did not express confidence in the birth process, their ability to give birth, the system for transfers and/or the primary unit as a birthplace, although they did express confidence in their midwife. Key conclusions and implications for practice birthplace is a profoundly important aspect of women׳s experience of childbirth. Birthplace decision-making is complex, in common with many other aspects of childbirth. A multiplicity of factors needs converge in order for all those involved to gain the confidence required to plan what, in this context, might be considered a 'countercultural' decision to give birth at a midwife-led primary maternity unit.